AB0936 Usefulness of Salivary Glands Ultrasonography in The Diagnosis of Sjögren Syndrome. (15th July 2016) - Paredes, B.; De Miguel, E.; Bonilla, G.; Pieren, A.; Plasencia, C.; Monjo, I.; Pieren, A.; Moral, E.; Tornero, C.; Rosell, A.; Ruiz-Bravo, E.; Martin-Mola, E.; et al.
Abstract : Background: Sjögren syndrome (SS) is a chronic autoimmune disease characterized by lymphocytic infiltration of the lacrimal and salivary glands resulting in clinical symptoms of keratoconjunctivitis sicca and xerostomia. Recent studies have shown that salivary gland ultrasonography (SGUS) is a valid tool to evaluate the involvement of major salivary glands in SS. Objectives: To assess the utility and accuracy of the USGS for diagnosis of SS. Methods: Single-center experimental study in a cohort of patients with suspected SS in whom a salivary gland biopsy (SGB) would be performed as requested by their usual physician. SGUS examination of the parotid and submandibular salivary glands was preformed prior to the realization of minor salivary gland biopsy. Changes in the echostructure of the glands were scored according to the scoring system of de Vita et al., which mostly focuses on the inhomogeneity of gland tissue with scores ranging from 0 to 3 (0: homogenous glands, 1: isolated hypoechoic areas, 2: scattered hypoechoic areas with variable size, not uniformly distributed, and/or to multiple punctate or linear non-shadowing densities and 3: large round or confluent hypoechoic areas, and/or to linear densities, and/or to multiple cysts or multiple calcifications). The SGB was considered as Gold standard. The definitive diagnosis of SS was made according to the AECG criteria. Results: From a sample of 24 patients with suspected SS, SGUS was performed in 20 patients before the SGB. All the patients were women with a mean age of 58±14. Eleven patients (46%) fulfilled AECG criteria, 4 (17%) did not met criteria and in 9 of them (37%) was not possible to classify because of insufficient data (at least two unregistered criteria). Eleven patients (55%) had a normal SGUS while 9 (45%) had some degree of changes in the gland's echostructure. In the group of patients who met AECG criteria, four (36%) had a negative biopsy, four (36%) positive biopsy and 3 (28%) had nonspecific biopsy. Of the 9 patients with an uncertain diagnosis for lack of data, 7 (78%) had a nonspecific biopsy. 5 patients (56%) with changes in the SGUS met AECG criteria. Of the 6 patients with positive biopsy for SS, 4 (67%) had ultrasound abnormalities. Of the 7 patients with pathological salivary scintigraphy, 5 (71%) had alterations in USGS. Taking biopsy as the gold standard, the sensitivity of the SGUS was 100%, specificity was 68.75%, PPV 44.4% and NPV of 100%; the sensitivity of scintigraphy was 80%, specificity was 44%, PPV 44% and NPV 44%. Considering the scintigraphy as the gold standard, sensitivity of ultrasound was 71.4%, specificity was 100%, PPV 100% and NPV 60%. As limitations of this study is important to remark that these are preliminary results from a small sample in early stages of the disease. Conclusions: Our findings suggest the potential of SGUS as a diagnostic tool for distinguishing SS. Although data is preliminary we found high sensitivity and NPV of SGUS compared to biopsy and high specificity of SGUS compared to scintigraphy. Disclosure of Interest: None declared